Biologia de nidificação e estrutura sociogenética de ninhos de Trypoxylon (Trypargilum) albitarse Fabricius 1804 (Hymenoptera: Crabronidae): comportamento de guarda do macho e paternidade - Almeida, Juliano Costa de (Universidade Federal de São Carlos, 2010)
Crabronid wasps of the genus Trypoxylon are characterized by being solitary and nest in preexisting cavities or in mud nests. The species Trypoxylon (Trypargilum) albitarse is included in the latter group, because builds its own mud nests. These nests are made by mud tubes with the lower portion open. Each tube is internally formed by a linear series of cells provisioned with captured spiders in which she oviposits an egg. After that, she starts closing the cell with a mud wall and begins to supply the next cell. Males of these wasps have an unusual behavior among the Hymenoptera. They assist the females during the construction and the provisioning of their nests, besides expelling parasites or other males who eventually approach the nest. This peculiarity of the male guard was always associated with his paternity of female offspring of the guarded nest. However, this hypothesis has not been tested until now, doing this the main objective of this work. The nesting behavior of the species Trypoxylon albitarse was monitored. For this, it took the observation of the nesting pairs and their collecting, as the collect of their offspring. The adults caught were frozen at -20°C for the genetic analysis. The offspring was collected after the construction of the cocoon and, after its emergence, it was weighted and frozen at -20°C for the same purpose. The monitoring of nesting allowed gathering data from this species, adding information to this gender, since most of that is gathered with trap nests. It was seen that that species have more nesting activity in cold and dry seasons, the emergence of adults is mainly concentrated in two moments, before and after the winter. Besides that, most of the larvae spend the winter in a quiescence state. A secondary sex ratio 1:1 was observed in two populations, São Carlos and Araras, however the resource allocation was higher for females, since they are 28% larger than males. To the paternity tests of the guard male, it was necessary to develop a genomic library for Trypoxylon albitarse, which allowed the development of eight microsatellite markers. Four of those were polymorphic and good enough to the purpose of these tests. These genetic tools were the first developed for this gender. They, together with the field observations, allowed assigning the female offspring of a nest to the male who guarded it. However, usurpation and extra-pair copulations were also found, contributing for greater understanding of mating system in this species and the understanding of the functional significance of the male guard behavior. The occurrence of diploid males was detected and their origin discussed.
Keywords: Evolução; Inseto; Microssatélite; Ecologia; Genética; CIENCIAS BIOLOGICAS::GENETICA